2012
DOI: 10.1002/bjs.7796
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative short-course radiotherapy with delayed surgery in primary rectal cancer

Abstract: The SRT-delay schedule was a feasible alternative with low toxicity. The study indicated a downstaging effect of SRT if surgery was delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 93 publications
5
104
1
2
Order By: Relevance
“…However, if SCPRT is followed by a gap of several weeks prior to surgery, then significant downstaging does occur [19]. Rectal cancers can be described as 'operable' if disease does not threaten or involve the surgical CRM.…”
Section: Introductionmentioning
confidence: 99%
“…However, if SCPRT is followed by a gap of several weeks prior to surgery, then significant downstaging does occur [19]. Rectal cancers can be described as 'operable' if disease does not threaten or involve the surgical CRM.…”
Section: Introductionmentioning
confidence: 99%
“…В нашем исследовании частота возникновения токсичности III-IV степени тяжести сравнима с пока-зателями, представленными в публикациях по пролон-гированной ХЛТ (14,6-18,2 %), но выше, чем 3,2-5,4 % при проведении короткого курса ЛТ [13][14][15]. Проктит III степени зарегистрирован у 3 (3,7 %) пациентов, из них у 1 впоследствии развилась несостоятельность анастомоза.…”
Section: Discussionunclassified
“…Small bowel toxicity with an increased risk for bowel obstruction is probably the most frequent side effect (5,36,37). The incidence of severe radio toxicity with leukopenia, abdominal pain and diarrhea is around 5% (38,39). The late effects of RT may add to the complications of pelvic surgery.…”
Section: The Biological Phasementioning
confidence: 99%
“…The risk for secondary cancer is increased after irradiation (36) Several studies have demonstrated that LRT and SRT with delay have comparable down staging effect and reduction in the rate of local recurrence (38)(39)(40). There is a clear doseresponse between the RT-dose and the tumour down staging when the same fractionations are compared (35,41).…”
Section: The Biological Phasementioning
confidence: 99%